2019
DOI: 10.1002/adsc.201900222
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Reduction of α‐Keto Thioesters with Hydrosilanes at Room Temperature: Divergent Synthesis through Reagent‐Controlled Chemoselectivities

Abstract: The combination of hydrosilanes with a Brønsted or Lewis acid as a promoter can be used for the reagent-controlled chemoselective reduction at room temperature of conjugated C=C bond, enone moiety, or the carbonyl of (β,γ-unsaturated) α-keto thioesters, providing facile access to β,γ-saturated α-keto thioesters, αhydroxy thioesters, or silyl ethers. The reaction pathway and the chemoselectivity can be fine-tuned through the judicious choice of the hydrosilane or the reaction conditions. The reactions tolerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…The requisite dienones 1 were readily prepared in pure form from the corresponding α‐keto thioesters or esters following our previous reports. When 1 a was kept at ambient temperature (30 °C), 3 a was formed within a few days in 45% yield along with 50% of the recovered starting materials (Table , entry 1); the yellow crystalline solid slowly turned to a light green gummy liquid with the progress of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The requisite dienones 1 were readily prepared in pure form from the corresponding α‐keto thioesters or esters following our previous reports. When 1 a was kept at ambient temperature (30 °C), 3 a was formed within a few days in 45% yield along with 50% of the recovered starting materials (Table , entry 1); the yellow crystalline solid slowly turned to a light green gummy liquid with the progress of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Unsymmetrical thioethers 100 a – c could thus be synthesized using 2.0 equivalent polymethylhydrosiloxane (PMHS)/1 mol% B(C 6 F 5 ) 3 via reductive deoxygenation of both the carbonyl groups (Scheme 55). The reactions tolerated a wide range of functional groups and the products were generally obtained in moderate to excellent yields [82] . The difference in outcome in Scheme 54 (with hydrosilanes containing one Si−H) and Scheme 55 (with PMHS containing multiple Si−H bonds) may be explained on the basis of the “dual Si−H effect” of PMHS, in which two proximate Si−H groups cooperatively accelerate the reductive deoxygenation of the α‐ketothioesters to unsymmetrical thioethers 100 (Scheme 55).…”
Section: Reactions Of α‐Ketothioestersmentioning
confidence: 98%
“…Das et al. found that it is possible to use inexpensive and commercially available hydrosilanes as reducing agents for the chemoselective reduction of the keto group of α‐ketothioesters 4 at room temperature [82] . It should be noted that hydrosilanes are mild, practical, and selective reducing agents and their reactivity can be fine‐tuned by changing the substituents on the silicon atom [83] .…”
Section: Reactions Of α‐Ketothioestersmentioning
confidence: 99%
See 2 more Smart Citations